The importance of appropriate reporting and investigation of incidental findings on computed tomography attenuation correction images during myocardial perfusion scintigraphy - Delaney, Francis T; Gray, Emma L; Lee, Joseph C (World Journal of Nuclear Medicine, 2019)
We present a case of lung cancer incidentally detected as a pulmonary nodule on computed tomography attenuation correction (CTAC) images during myocardial perfusion scintigraphy (MPS). Unfortunately, the incidental lesion was not fully investigated following MPS report and had developed into metastatic lung carcinoma when diagnosed over 1 year later, with failure of subsequent emergent chemotherapy. The disease appeared to be localized when initially detected during MPS. This case highlights the importance and potential clinical value of routine review of CTAC images in MPS with appropriate reporting and further investigation of suspicious incidental findings. In addition, the importance of effective communication between nuclear medicine department and treating team is clear to ensure suspicious incidental findings are given sufficient credence and thoroughly investigated promptly to avoid adverse clinical outcomes.
Keywords: Computed tomography attenuation correction; incidental findings; low-dose computed tomography; lung carcinoma; myocardial perfusion scintigraphy